1994
DOI: 10.1046/j.1471-4159.1994.63020612.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Manganese Superoxide Dismutase by Cytokines and Lipopolysaccharide in Cultured Mouse Astrocytes

Abstract: To determine whether cytokines or lipopolysaccharide (LPS) are involved in the induction of superoxide dismutase (SOD) in the nervous system, we examined the effects of these substances on the levels of SOD in cultured mouse astrocytes. Treatment of astrocytes with 102 to 104 U/ml tumor necrosis factor‐α for 3 days increased the levels of Mn SOD in a dose‐ and time‐dependent manner to as much as six times the level under nontreated conditions. Treatment with 1.0 µg/ml LPS for 3 days elicited a fourfold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 32 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…Sod2 is an intramitochondrial free radical scavenging enzyme, dismutates reactive oxygen radical species (ROS) to hydrogen peroxide and molecular oxygen and prevents accumulation of superoxides in cells. Its upregulation in our study in contrast to Sod1 and Cat is in accordance with observations of other groups that have reported that LPS increases Sod2 activity, protein or mRNA in vitro in (brain) cell cultures (Kifle et al, 1996;Kramer et al, 2002;Mokuno et al, 1994;Visner et al, 1990;Yu et al, 1999) or in vivo (Bordet et al, 2000), but not Sod1 (Kramer et al, 2002;Mokuno et al, 1994;Visner et al, 1990;Yu et al, 1999) or Cat (Bordet et al, 2000). In our study we could show that the induction of Sod2 in astrocytes is rather an indirect effect due to LPS-induced microglial activation than a direct effect of LPS, which is in accordance with other studies that Sod2 is induced by proinflammatory cytokines like IL-1 or TNF-a in glial cell cultures (Kifle et al, 1996;Mokuno et al, 1994;Visner et al, 1990), both cytokines well known to be secreted by activated microglia.…”
Section: Discussionsupporting
confidence: 93%
“…Sod2 is an intramitochondrial free radical scavenging enzyme, dismutates reactive oxygen radical species (ROS) to hydrogen peroxide and molecular oxygen and prevents accumulation of superoxides in cells. Its upregulation in our study in contrast to Sod1 and Cat is in accordance with observations of other groups that have reported that LPS increases Sod2 activity, protein or mRNA in vitro in (brain) cell cultures (Kifle et al, 1996;Kramer et al, 2002;Mokuno et al, 1994;Visner et al, 1990;Yu et al, 1999) or in vivo (Bordet et al, 2000), but not Sod1 (Kramer et al, 2002;Mokuno et al, 1994;Visner et al, 1990;Yu et al, 1999) or Cat (Bordet et al, 2000). In our study we could show that the induction of Sod2 in astrocytes is rather an indirect effect due to LPS-induced microglial activation than a direct effect of LPS, which is in accordance with other studies that Sod2 is induced by proinflammatory cytokines like IL-1 or TNF-a in glial cell cultures (Kifle et al, 1996;Mokuno et al, 1994;Visner et al, 1990), both cytokines well known to be secreted by activated microglia.…”
Section: Discussionsupporting
confidence: 93%
“…The elevation of SOD is mainly attributed to an overreaction to the augmented ROS after ischemic injury, this was confirmed by a number of investigations which suggest increased immunoreactivities of SOD in different areas of brain following a cerebrovascular accident from clinical examination (Gruener et al 1994) and animal model evaluation (Danielisová et al 2005;Liu et al 1993;Matsuda et al 2009;Ohtsuki et al 1993). Another possible reason for this phenomenon is the role of cytokines in the regulation of SOD activity (Mokuno et al 1994). It has been demonstrated that a number of cytokines are upregulated in resident brain cells after a stroke (Wang et al 2007), which may mediate the elevated activity of SOD.…”
Section: Discussionmentioning
confidence: 76%
“…It is known that the induction of SOD2 can be mediated by various macromolecules, such as interleukyn-1 [50], lipopolysaccarides [51], and tumor necrosis factor- α [52]; furthermore, thiol-reducing agents can affect SOD2 biosynthesis, as demonstrated by the enhanced SOD2 expression caused by thioredoxin, a potent disulfide oxidoreductase [31]. In this paper, the addition of a heterologous thioredoxin to diclofenac-treated cultures of SH-SY5Y led to an enhancement of the SOD2 levels, as well as to a reduction of the apoptosis.…”
Section: Discussionmentioning
confidence: 99%